PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK BERKIRIM SALAM DAN SOAL TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMPN 1 RANAH BATAHAN KABUPATEN PASAMAN BARAT - -, Isnayarni - (Pendidikan Matematika, 2014)
This research was conducted by conceptual understanding of student had low and unwilling to ask questions and rarely hold a discussion. This was an experimental research which used random the subject design. The population of the research was all of the first year students of SMPN 1 Ranah Batahan registered in academic year 2013/2014. As the sample, the students in class VII1 was taken as the experimental group, and those in class VII3 was chosen as the control group. The instrument of the research was an essay post-test whose reliability was . The data gotten was analyzed by using MINITAB. The resultf of data analysis showed that was 0,041 wich was smaller than . Thus, it was concluded that the use of chained-greeting and questions technique could improve the conceptual understanding student mathematics the better than the use of convensional learning in the first year of SMPN 1 Ranah Batahan Kabupaten Pasaman Barat.